Actinotetraoses A–H: Tetrasaccharide Derivatives from a Grasshopper-Associated Amycolatopsis sp. HCa1 - Guo, Zhi Kai; Zhang, Gao Fei; Jiao, Rui Hua; Shen, Yan; Xu, Qiang; Tan, Ren Xiang; Ge, Hui Ming (Planta Medica, 2012)
Chemical investigation of the insect-derived actinomycete Amycolatopsis sp. HCa1 with NMR-guided fractionation led to the isolation of eight new tetrasaccharide derivatives containing an unusual nonreducing glucotetraose skeleton, named actinotetraoses A–H (1–8), and one known compound, tigloside (9). The structures of these compounds were determined on the basis of analyses of their spectroscopic data. The in vitro immunosuppressive activity and cytotoxicity of these compounds were evaluated by T cell viability and MTT assays, respectively. Only actinotetraose E (5) displayed weak immunosuppressive activity.
Keywords: Amycolatopsis; Pseudonocardiaceae; insect-derived actinomycete; tetrasaccharide derivatives